Implementasi Algoritme Enkripsi Grain-128 pada Sistem Pemantauan Elektrokardiogram berbasis Protokol MQTT-SN - Iwi Suharti; Ari Kusyanti; Fariz Andri Bakhtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Message Queuing Telemetry Transport for Sensor Networks (MQTT-SN) is a publish-subscribe communication protocol for Wireless Sensor Networks (WSN), which developed to guarantee the needed of publish-subscribe protocol which can be applied for sensor networks which doesn't have network interface. However, MQTT-SN has a weakness because by default MQTT-SN sends plaintext in transmission process, it proves that MQTT-SN don't guarantee security aspect of confidentiality. Security mechanism is needed to ensure confidentiality of MQTT-SN especially in its use as a communication protocol in healthcare system, because in health sector data confidentiality is important. Security mechanism to ensure MQTT-SN confidentiality has been conducted using Advanced Encryption Standard 128 (AES128), which is a conventional cryptographic algorithm with high computational process which not appropriate with WSN characteristics, in addition computational defects has been found in all types of AES, so an alternative algorithm is needed to replace AES. This research provides an alternative solution by applying end-to-end security mechanisms for publishers and subscribers using lightweight stream cipher Grain-128 on prototype electrocardiogram monitoring system based on MQTT-SN. The results showed that, this security mechanism successfully secured electrocardiogram data transmitted on MQTT-SN protocol from confidentiality. Grain-128 performs better than AES128 based on encryption time and memory usage.